1959
DOI: 10.1002/pol.1959.1204113801
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of semicrystalline polymers. Part I. The effect of temperature on the oxidation of polyolefins

Abstract: Oxidation rates of several uninhibited polyolefins were determined in the temperature range 40–140°C. The logerithm of the induction period increased linearly with 1/T, no changes in slope being noted in the melting range with polythylene. At the lower temperatures branched polythylenes were more susceptible to oxidation than the linear types. In the solid statem, oxygen uptake of both modifications were substantially less than that observed for the molten polymer. The amount of oxygen reacting in the solid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1961
1961
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(27 citation statements)
references
References 7 publications
4
23
0
Order By: Relevance
“…As a result it can be expected that PE only degrades in the amorphous phase. Experimentally this is confirmed by Hawkins et al [80] and Winslow et al [81], they showed that with increasing crystallinity the oxidation rate of PE decreases. At the moment there is no doubt that oxidation in polyethylene and polypropylene is restricted to the amorphous phase [51], which is the case for the majority of all polymers.…”
Section: Effect Of Crystallinity and Stereoregularitysupporting
confidence: 61%
“…As a result it can be expected that PE only degrades in the amorphous phase. Experimentally this is confirmed by Hawkins et al [80] and Winslow et al [81], they showed that with increasing crystallinity the oxidation rate of PE decreases. At the moment there is no doubt that oxidation in polyethylene and polypropylene is restricted to the amorphous phase [51], which is the case for the majority of all polymers.…”
Section: Effect Of Crystallinity and Stereoregularitysupporting
confidence: 61%
“…Figure 37 illustrates the non -Arrhenian behavior of the induction time for pure PE and composite PENC at the three studied temperatures. It can be seen that experimental results correspond well with available literature data for polyethylene thermal degradation [140,153,154,155,156,157,158,159,160] . Finally, our results confirmed that induction time values follow a non Arrhenian behavior.…”
Section: Oxidation Kineticssupporting
confidence: 78%
“…If the mechanism of the reaction at higher or lower temperatures should differ, this too would alter the slope of the curve. Numerous examples of non-linear Arrhenius plots, the consequence of a change in mechanism, can be found in the literature [29][30][31][32].…”
Section: Permeance Propertiesmentioning
confidence: 99%